Tourism Sector Development Policy in Increasing Local Income in Gresik Regency - Fawaz Nurul Widad Farahani; Ika Devy Pramudiana; Dian Ferriswara; Sri Kamariyah (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This study examines tourism development policies and their contribution to increasing Regional Original Revenue (PAD) in Gresik Regency. The research specifically analyzes policy implementation, supporting and inhibiting factors, and their implications for local economic growth. Employing a qualitative descriptive approach, data were collected from key informants within the Gresik Regency Government, including the Office of Culture, Tourism, Youth, and Sports, as well as relevant supporting agencies. Primary data were supplemented with secondary sources, and analysis was conducted using McNabb’s (2002) model, which involves data grouping, interpretation, and the formulation of generalizable insights. Findings indicate that tourism development policies in Gresik Regency focus on five key areas: designation and spatial planning of tourism zones, development of tourist attractions and supporting infrastructure, promotion of tourism activities, and business development initiatives. These policies are supported by government regulations, community involvement, improved facilities, diversified tourism destinations, and marketing strategies utilizing both online and offline media. However, several inhibiting factors were identified, including limited funding, inadequate human resources, lack of cooperation with third parties, negative public perceptions, and insufficient knowledge about tourism potential. Overall, tourism in Gresik Regency demonstrates significant potential to enhance PAD, given its diverse natural, cultural, and religious attractions. The study concludes that strengthening collaboration, improving human resource capacity, and increasing promotional efforts are essential for optimizing tourism’s contribution to sustainable regional economic development. Future research should explore quantitative measurements of tourism's economic impact to validate the qualitative findings. Additionally, implementing performance-based budgeting for tourism programs may improve resource allocation and accountability.